2004
DOI: 10.1097/01.wcb.0000125887.48838.37
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hemodynamic Compromise by Cerebrovascular Reserve and Oxygen Extraction Fraction in Occlusive Vascular Disease

Abstract: Cerebrovascular reserve (CVR) and oxygen extraction fraction (OEF) are used to identify hemodynamic compromise in symptomatic patients with carotid occlusive vascular disease, but evidence suggests that they are not equivalent. The authors studied the relationship between CVR and OEF to evaluate their equivalence and stages of hemodynamic compromise. Symptomatic patients (N = 12) with carotid occlusion were studied by stable xenon-computed tomography CBF after intravenous acetazolamide administration for CVR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
56
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 37 publications
4
56
0
Order By: Relevance
“…In previous studies involving experimental stroke in baboons and humans (39,40), most of the tissue with the highest oxygen extraction fraction, the lowest rCBF, and an impaired cerebrovascular reserve went into a lacunartype of infarction earlier than tissue that was less severely affected. Furthermore, major reperfusion and lesser infarct growth predicted better neurological outcome after stroke (41).…”
Section: Discussionmentioning
confidence: 90%
“…In previous studies involving experimental stroke in baboons and humans (39,40), most of the tissue with the highest oxygen extraction fraction, the lowest rCBF, and an impaired cerebrovascular reserve went into a lacunartype of infarction earlier than tissue that was less severely affected. Furthermore, major reperfusion and lesser infarct growth predicted better neurological outcome after stroke (41).…”
Section: Discussionmentioning
confidence: 90%
“…On the other hand, recent studies analyzing a larger number of patients have proved that the decrease in CVR and increased OEF did not necessarily parallel each other (8,9). Nemoto et al (9) reported that about 40% of patients with reduced CVR had normal OEF (9). Subsequently, Kuroda et al (8) have also revealed that OEF was significantly elevated in about 40% of type 3 patients.…”
Section: Discussionmentioning
confidence: 96%
“…Many earlier studies have evaluated the relationships between OEF and CVR (8,9,13,14). Most of these studies have concluded that there is a significant correlation between OEF and CVR to acetazolamide (13,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies demonstrated that decreases in CVR and increases in OEF did not necessarily parallel each other. [63][64][65] PET measurements have been useful in demonstrating reversals of altered OEF because patients improve brain flow through collaterals 66 and following superficial temporal-to-MCA anastomoses. 67,14 Controlled studies to assess the value of OEF determinations for selection of therapy in patients with carotid occlusive disease are needed to determine the utility of these techniques.…”
Section: Asl Mr Perfusionmentioning
confidence: 99%